To solve this question, we use the factor theorem, and using it, the polynomial function is:
[tex]f(x) = x^3 - 2x^2 - 3x + 6[/tex]
------------------------------
The factor theorem means that if k is a root of f(x), f(k) = 0.
Thus, applying the factor theorem for this question, we have to choose the function for which: [tex]f(2) = 0, f(\sqrt{3}) = 0, f(-\sqrt{3}) = 0[/tex]
------------------------------
Function 1:
[tex]f(x) = x^3 - 2x^2 - 3x + 6[/tex]
Testing the values:
[tex]f(2) = 2^3 - 2(2)^2 - 3(2) + 6 = 8 - 8 - 6 + 6 = 0[/tex]
[tex]f(\sqrt{3}) = \sqrt{3^3} - 2(\sqrt{3})^2 - 3\sqrt{3} + 6 = \sqrt{3^2\times3} - 6 - 3\sqrt{3} + 6 = 3\sqrt{3} - 3\sqrt{3} = 0[/tex]
[tex]f(-\sqrt{3}) = -\sqrt{3^3} - 2(-\sqrt{3})^2 - 3(-\sqrt{3}) + 6 = -\sqrt{3^2\times3} - 6 + 3\sqrt{3} + 6 = -3\sqrt{3} + 3\sqrt{3} = 0[/tex]
Thus, since all three conditions are satisfied, [tex]f(x) = x^3 - 2x^2 - 3x + 6[/tex] is the polynomial function.
A similar question is given at https://brainly.com/question/11378552